Pesticide Provisions of the Florida Agricultural Worker Safety Act (FAWSA) - Fredrick M. Fishel (EDIS, 2019)
The purpose of this guide is to provide a summary of the pesticide provisions of the recently enacted Florida Agricultural Worker Safety Act (FAWSA) and the definitions that are used in its language. The pesticide provisions of FAWSA, which became effective on July 1, 2004, are designed to ensure that information is made available to farm workers about specific hazards associated with the use of agricultural pesticides. The law was implemented and will be enforced by the Florida Department of Agriculture and Consumer Services (FDACS), also known as “the Department.”